آيات تحويل القبلة دراسة تحليلية ودروس تربوية - أبو الفضل، أحمد عبدالسلام محمد Abu Alfadl, Ahmed Abdulsalam Mohammed (جامعة كفر الشيخ - كلية الآداب, 2019)
Praise be to Allah, Lord of all creation, accompllsh and permanently prayers and peace be upon our Prophet Muhammad and his family and all his companions. And then, This is a Research summary entitled: "Verses of the Qiblah change an analytical study and educational lessons". The structure of the research was organized into an introduction, a foreword, nine researches, and a conclusion. As for the introduction, it contains an indication of the study content, optional reasons for it and the methodology of the study. Second: The preamble contains a summary of the Qiblah conversion story, which is the study of verses. Third: The research plan, which included the interpretation of the verses of converting the Qiblah verse by verse, the total of which reached nine verses, singled out for each verse of a special topic, except for the fifth and sixth verses. Closer and paste, it came as follows: First mention the verse in the topic title. -The verse is appropriate for the preceding -The reason for its descent, If any Meanings of its vocabulary Judgments and related matters -The general meaning of the verse -List detailed lessons learned Fourth: Conclusion, which includes the results of the research, proved its review, and indexed the contents.
الحمد لله رب العالمين والصلاة والسلام الأتمان الأدومان على سيدنا محمد وعلى آله وصحبه أجمعين. وبعد،، فهذا ملخص بحث بعنوان: "آيات تحويل القبلة دراسة تحليلية، ودروس تربوية". وقد انتظم هيكل هذا البحث في مقدمة، وتمهيد، وثمانية مباحث، وخاتمة. أما المقدمة ففيها بيان لمحتوى البحث، وأسباب اختياري له، والمنهج المتبع في دراسته. ثانيا: التمهيد وفيه خلاصة عن قصة تحويل القبلة التي تدور حولها دراسة الآيات. ثالثا: خطة البحث، وقد اشتملت على تفسير آيات تحويل القبلة آية آية وقد بلغ مجموعها تسع آيات أفردت لكل آية منها مبحثا خاصا، إلا الآية الخامسة والسادسة فقد جعلتهما في مبحث معا، واتبعت كل آية بدروسها المستفادة منها؛ ليكون اللفظ للفظ أوفق، والمعنى للذهن أقرب وألصق، فجاءت على النحو التالي: -أذكر الآية أولا في عنوان البحث. -مناسبة الآية لما قبلها. -سبب نزولها إن وجد. -معاني مفرداتها. -الأحكام والمسائل المتعلقة بها. -المعنى العام للآية. -ذكر الدروس التربوية المستفادة منها مفصلة. -الخاتمة، وفيها نتائج البحث، وثبت مراجعه، وفهرس المحتويات.
Keywords: القرآن الكريم -- تفسير القرآن -- ألفاظ القرآن -- إتجاه القبلة